Immunomodulatory potential of primary cilia in the skin - Sun, Jingwei; Yuan, Huimin; Yu, Yanru; Li, Aorou; Zhao, Zihe; Tang, Yang; Zheng, Fengjie (Frontiers in Immunology, 2024)
Primary cilia (PC) are essential signaling hubs for proper epithelial formation and the maintenance of skin homeostasis. Found on most cells in the human body, including skin cells, PC facilitate signal transduction that allows ciliated cells to interact with the immune system via multiple pathways, helping to maintain immune system homeostasis. PC can be altered by various microenvironmental stimuli to develop corresponding regulatory functions. Both PC and ciliary signaling pathways have been shown to be involved in the immune processes of various skin lesions. However, the mechanisms by which PC regulate cellular functions and maintain immune homeostasis in tissues are highly complex, and our understanding of them in the skin remains limited. In this paper, we discuss key ciliary signaling pathways and ciliated cells in the skin, with a focus on their immunomodulatory functions. We have compiled evidence from various cells, tissues and disease models to help explore the potential immunomodulatory effects of PC in the skin and their molecular mechanisms.